THE IMPACT OF MONETARY POLICY ON BANK CREDIT DURING ECONOMIC CRISIS: INDONESIAS EXPERIENCE - Abdul Mongid (University of Merdeka Malang, 2008)
The monetary policy mechanism by which monetary policy was transmitted to thereal economy had emerged as the pivotal discussion topic recently. This paper tried to discussthe impact of Bank Indonesias monetary policy on loan bank. By using simple loan bankframework we concluded that monetary policies were able to influence loan bank. Themonetary variables such as discount rate policy, base money and exchange rate policy werevery important in determining the banking credit. As the credit was very important to influencesthe economic activitiy, the result provided evidence that monetary policy was important as atool to control economic activity via credit channel. The validity of this study challenged thehypotheses that monetary policy was death. However, monetary policy maker should carefullyconsider the soundness of the banking industry because it was a strategic partner for monetaryauthority to control the economic activities.